Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Keterampilan Berpikit Kritis Siswa Madrasah Ibtidaiyah Swasta Nurul Ittihad Kota Jambi - Rengganis Diladias; Andi Nurhasanah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research is motivated by the low critical thinking skills of fifth-grade students at SDN Nurul Ittihad, Jambi City. Critical thinking skills are very important for students to face challenges in the modern era, so appropriate learning strategies are needed to develop them. This research aims to improve students' critical thinking skills through the application of a guided inquiry learning model in Natural and Social Sciences (IPAS) subjects. The research method used is Classroom Action Research (CAR) with reference to the Kemmis and McTaggart model which includes four stages, namely planning, implementation and observation, reflection, and re-planning. This research was conducted in two cycles, each consisting of three meetings. Data were collected using documentation, tests, interviews, and observations to measure the increase in student engagement, teacher activity, and learning outcomes that reflect critical thinking skills. The results showed a significant increase in several indicators. Student engagement increased from 87% in cycle I to 92% in cycle II. Teacher activity also increased from 71% in cycle I to 83% in cycle II. Meanwhile, the percentage of students achieving learning mastery increased sharply, from 21% before the intervention to 68% in Cycle I, and 89% in Cycle II. These findings indicate that the implementation of the guided inquiry model can actively and purposefully improve students' critical thinking skills. This model effectively encourages students to become more involved in the learning process, ask questions, explore information, and develop a deeper understanding of the subject matter.